Odpowiedzi

2010-01-17T11:50:55+01:00
A)3(2x-1)-5(x-3)+6(3x-4)= 6x-3 -5x+15 +18x-24=19x-12
b)0,2x+0,5x+5(5x-1)-2,7x=6,5
0,2x+0,5x+25x-5-2,7x=6,5
23x=11,5
x=0,5
c)0,3(0,4-1,2)+0,36x=0,6
0,12-0,36+0,36x=0,6
0,36x=0,84
x=2, 3333...
Najlepsza Odpowiedź!
2010-01-17T11:55:58+01:00
A)3(2x-1)-5(x-3)+6(3x-4)
6x-3-5x+15+18x-24=19x-12

b)0,2x+0,5x+5(5x-1)-2,7x=6,5
0,2x+0,5x+25x-5-2,7x=6,5
0,2x+0,5x+25x-2,7x=6,5+5
23x=11,5 /:23
x=0,5

c)0,3(0,4-1,2)+0,36x=0,6
0,12-0,36+0,36x=0,6
0,36x=0,6-0,12+0,36
0,36x=0,84 /*100
36x=84 /:36
x=84/36
x=2 1/3
2010-01-17T11:56:26+01:00
A ) 3*(2x-1)-5*(x-3)+6*(3x-4) =
6x-3-5x+15+18x-24 =19x-12

b)0,2x+0,5x+5(5x-1)-2,7x=6,5
0,2x+0,5x+25x-5-2,7x=6,5

23x =11,5 /:23
x=0,5

c)0,3(0,4-1,2)+0,36x=0,6
0,12-0,36+0,36x=0,6
0,36x=0,84
x=2, 3333..